KADAR TIMBAL (Pb) DALAM URINE TERHADAP LAMANYA PEDAGANG KAKI LIMA BERJUALAN DI PASAR 45 KOTA MANADO - Suwarja Suwarja; Julice Sopiti; Agus Rokot (Jurnal Kesehatan Lingkungan, 2019)
Lead is a metal that is very dangerous and toxic to humans, which can be derived from the act of consuming food, drink or inhalation from the air, dust contaminated with Pb, contact with skin, contact with eyes and through parental. Lead can cause air pollution due to motor vehicle emissions gas. Street vendors are one of the groups that can be exposed to Pb. The purpose of this study was to determine the relationship of lead levels (Pb) in urine to the length of street vendors selling at the 45 markets of Manado City. This research uses observational analytic method with cross sectional design. The sample in this study were all street vendors selling from zero points to the front of jumbo in Pasar 45. Purposive Sampling was carried out by sampling. The results of this study showed that the average length of work was 12 hours, the average lead level in urine for all samples was 0.8461 mg / L which had exceeded the threshold value of 0.15 mg / L. Statistical test results using Pearson Product Moment correlation show there is no significant relationship between work duration and levels of Pb in urine (r = -0.024, p = 0.899). The conclusion of this study is that there is no relationship between lead levels (Pb) in urine with the length of street vendors selling at the 45 markets of Manado City.